REGIONAL POTENTIAL-BASED DEVELOPMENT PLANNING: A STUDY OF LOCATION QUOTIENT, SHIFT SHARE, AND KLASSEN TYPOLOGY IN TULANG BAWANG REGENCY - Etika Revolusi Nusantari (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the structure and economic potential of Tulang Bawang Regency for the 2019–2023 period as the basis for development planning based on regional potential. Three quantitative approaches are used in an integrated manner, namely Location Quotient (LQ) to identify the base sector, Shift Share to assess the contribution of sectoral growth, and the Klassen Typology to group sectors based on their growth and contribution to GDP. The results of the analysis show that the Agriculture and Processing Industry sector is the base sector with an LQ value of > 1. In general, the economic growth of Tulang Bawang Regency is dominated by national influence, but some sectors such as Agriculture, Trade, and Education show local competitive advantages. Klassen's typology identifies the Processing, Information and Communication Industries, and Government Administration sectors as developed and fast-growing sectors, while the Construction, Transportation, and Social Services sectors are classified as lagging behind. These findings recommend strengthening leading sectors and strategic interventions in potential and underdeveloped sectors to support inclusive and sustainable regional economic development.